Implementasi Collaborative Governance Dalam Pelayanan Ijin Usaha Melalui Online Single Submisssion (OSS) Di Desa Penatih Dangin Puri Kecamatan Denpasar Timur - Ni Luh Putu Ening Permini; Cokorda Putra Indrayana; Cok Gde Agung Kusuma Putra; I Kadek Widi Nugraha; AA Anom Sawitri (Lembaga Pengembangan Kinerja Dosen, 2023)
The government is required to always adjust to what is needed by the community, one of which is the need for decent public services. Collaboration is a stage to give birth to a service innovation in the public sector, therefore collaboration in innovation seems endless to always be discussed by the government as well as organizations and other sectors. In the last ten years, the practice of collaboration and innovation in the administration of the government bureaucracy in Indonesia has been revealed in a number of literatures. One of them is in Penatih Dangin Puri Village, East Denpasar District. According to Government Regulation Number 17 of 2018 concerning sub-districts, it is stated that the task of the Perbekel is in the field of service in the working area. In accordance with the mandate of the government regulation, one form of service in Penatih Dangin Puri Village is business license services through Online Single Submission (OSS), land services, and non-licensing services. The purpose of this research is to find out the collaboration process in the implementation of business license services through the Online Single Submission (OSS) system in Penatih Dangin Puri Village, East Denpasar District and to determine the achievement of collaboration results in the implementation of business license services through the Online Single Submission (OSS) system. in Penatih Dangin Puri Village, East Denpasar District. The theory used by Penta Helix Collaborative according to Howkis (2009: 34) is, optimizing the role of academic, business, community, government and media (ABCGM), in developing goals because it relates to policies made by the government because this theory is a breakthrough and new strategy in In this millennial era, some regional heads have even made the Pentha Helix concept a new strategy to deal with several problems that occur in the region. This study uses a qualitative approach where the qualitative approach is an approach based on the philosophy of postpositivism, while for researching on natural objects, where the researcher is the key instrument, the data collection technique is done by triangulation (combined). Where data analysis is inductive/qualitative, and qualitative research results emphasize the meaning of generalization. Researchers have made direct observations to Penatih Dangin Puri Village. In addition, the authors also conducted observations and documentation studies on existing documents and policies, as well as in-depth interviews with all informants related to the implementation of the Online Single Submission (OSS) permit service.